2013
DOI: 10.1016/j.chembiol.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecules for Dissecting Endomembrane Trafficking: A Cross-Systems View

Abstract: Endomembrane trafficking has a key role for ensuring homeostasis, growth and development, hormonal signaling, and adaptation of eukaryotes to the constantly changing environmental conditions. The complex organization of the endomembrane system implies the need for searching novel tools to specifically probe the regulatory components and dissect the tightly interconnected vesicle transport pathways. Here, we review the large-scale chemical genetic screens, which led to the identification of small molecules with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 94 publications
0
38
0
Order By: Relevance
“…VTI12 also is used as a TGN marker (Geldner et al, 2009). Likewise, the treatment of brefeldin A (BFA) and wortmannin, endomembrane trafficking inhibitors (Hicks and Raikhel, 2010;Mishev et al, 2013), induced the formation of BFA compartments and ringlike structures of SCYL2B proteins (Supplemental Fig. S11).…”
Section: Discussionmentioning
confidence: 99%
“…VTI12 also is used as a TGN marker (Geldner et al, 2009). Likewise, the treatment of brefeldin A (BFA) and wortmannin, endomembrane trafficking inhibitors (Hicks and Raikhel, 2010;Mishev et al, 2013), induced the formation of BFA compartments and ringlike structures of SCYL2B proteins (Supplemental Fig. S11).…”
Section: Discussionmentioning
confidence: 99%
“…The endomembrane system is composed of specific membrane-delimited organelles, such as the endoplasmic reticulum, Golgi apparatus/TGN, plasma membrane, endosomes (early and late endosomes) and prevacuolar compartments/multivesicular bodies (Mishev et al, 2013;Shoji et al, 2014). Recently, accumulating evidence has shown that endomembrane trafficking and related organelles have a key role in maintaining physiological processes and pathogenicity in filamentous fungi (Shoji et al, 2014).…”
Section: Researchmentioning
confidence: 99%
“…Over the recent years though, plant biology has witnessed an increasing interest in chemical biology approaches for processes such as endomembrane trafficking, hormonal signaling and primary and secondary metabolism (Hicks and Raikhel, 2012; Mishev et al, 2013; Tresch, 2013; Ma and Robert, 2014). Depending on which aspect of plant biology the small molecule of choice is affecting, and what the intended use will be, knowledge on the interactome of the small molecule might be essential.…”
Section: Future Perspectivesmentioning
confidence: 99%